Mutli-element system reliability using markov chain model - Kotes, Peter; Vican, Josef (Communications - Scientific letters of the University of Zilina, 2004)
Up to now our researches have focused on determining the existing bridge element reliability level. However, the real structures occurring in practice are not just one-element structures, but they are a set of multiple elements with various signification of single element in structure. On this account, current research activities were focused on determining multi-element structure reliability level. In the presented paper, the steel grid system with m-elements subjected to bending was considered. The Markov chain models were used to calculate structure reliability. The results are compared with analytic solution of system reliability. Analogously, the degradation of material properties and its influence on reliability of overall multi-element grid system was considered.